2008
DOI: 10.1111/j.1479-8301.2007.00209.x
|View full text |Cite
|
Sign up to set email alerts
|

A case of vascular depression associated with musical hallucinations successfully treated with paroxetine and a low dose of risperidone

Abstract: Herein, we report a case of an 83-year-old man with vascular depression associated with musical hallucinations. Brain magnetic resonance imaging disclosed diffuse brain atrophy with multiple higher-density zones in the white matter and basal ganglia. Single photon emission computed tomography images showed areas of hypoperfusion in the bilateral temporal lobe and basal ganglia. Combination treatment with paroxetine and a low dose of risperidone rapidly improved both the depressive symptoms and musical hallucin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…The Ser9Gly polymorphism of dopamine receptor D3 (DRD3) could disturb the membrane insertion of Psychiatry and Clinical Neurosciences 2011; 65: [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] Pharmacogenomics of schizophrenia 7 this receptor molecule with biological consequence. Studies with FGA treatment response showed the Gly allele is more frequent among poor responders, however, recent studies with SGA showed a positive link of the Gly allele with a better response.…”
Section: Dopamine Receptor D3mentioning
confidence: 99%
See 4 more Smart Citations
“…The Ser9Gly polymorphism of dopamine receptor D3 (DRD3) could disturb the membrane insertion of Psychiatry and Clinical Neurosciences 2011; 65: [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] Pharmacogenomics of schizophrenia 7 this receptor molecule with biological consequence. Studies with FGA treatment response showed the Gly allele is more frequent among poor responders, however, recent studies with SGA showed a positive link of the Gly allele with a better response.…”
Section: Dopamine Receptor D3mentioning
confidence: 99%
“…The neurobiology of DISC1 in the normal developing and adult brain and its roles in SCZ are not well understood. The biological role of DISC1 is, however, speculated from the following findings: (i) downregulation of DISC1 accelerates morphological development of adult-born neurons resulting in soma hypertrophy and enhancement of dendritic outgrowth; (ii) inhibition of DISC1 leads to mispo-Psychiatry and Clinical Neurosciences 2011; 65: [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] Pharmacogenomics of schizophrenia 9 sitioning of new neurons in the molecular layer from overextended migration, suggesting that DISC1 serves as an interpreter that relays positional signals to the intracellular migratory machinery rather than a direct mediator of neuronal migration; (iii) new neurons with DISC1 knockdown exhibit more mature neuronal firing patterns; and (iv) downregulation of DISC1 accelerates synapse formation of newborn neurons. Taken together, these results indicate that DISC1 controls the tempo of the entire process of neuronal integration in the adult brain as a master regulator.…”
Section: Disrupted In Schizophreniamentioning
confidence: 99%
See 3 more Smart Citations